Management of Family Medicine Approach to Mrs. S Patients, 36 Years-Old Female with Schizophrenia Residual F20.5 Condition - Mayangsari, Ayu; Romadhon, Yusuf Alam (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: This study aims to identify risk factors, clinical problems and provide patient management with the implementation of holistic family doctor services based on an evidence-based medical approach with an imaginative approach to patients and families. Methodology: This research is a case report. Primary data were obtained through anamnesis (directly from the patient and indirectly from family members), physical examination, and home visits to complete family, psychosocial, and environmental data. Secondary data was obtained from the patient's medical records at the puskesmas. Assessment is based on a holistic diagnosis from the beginning, process, and end of the quantitative and qualitative studies. Results: A 36-year-old woman was diagnosed with schizophrenia. The patient acknowledged the presence of mental disorder in herself. The results of the evaluation showed that patient complaints and worries were reduced, patient and family knowledge about schizophrenia was lacking and needed further education. Conclusion: Schizophrenia that occurs in patients is caused by a lack of attention from parents and also families who do not socialize with neighbors and family.